Интенсивное культивирование штаммов гриба Pleurotus ostreatus (Jacq.:Fr.) Kumm. на твердых отходах растительной биомассы - Вовк, Н.В. (Промышленная ботаника, 2002)
The features of fruiting of the P. ostreatus strains (17M, H-7, Kp-93, F, C-085, HK-35) cultivated on the hard wastes of plant biomass are presented in the work. It is determined that the husk of sunflower is more preferable for 17M, HK-35 and Kp-93 strains to be cultivated on, yet for the HK-35 strain cultivation the straw of wheat is more acceptable. It is ascertained that calculated coefficient of habitus (K) is a relatively constant parameter for all P. ostreatus strains, and depend neither on carbon substratum nor fruitage indeces of the studied strains. Calculated coefficient correlation between two coefficients of habitus (K husk and K straw) for the strains was 0,938.